Asian Century... on a Knife-edge A 360 Degree Analysis of Asia's Recent Economic Development - West, John (Springer Singapore, 2018)
This book is open access under a CC BY 4.0 license. This book delves into the widely held belief that the 21st century will be the "Asian Century" by examining the Asia's rapid economic development in the post-war era and the challenges it faces in forging ahead of world leaders in the West. The impact of the current turbulent global political climate on Asia is critically analyzed, employing a holistic and multidisciplinary approach, combining economic, social, political and geopolitical perspectives. Written in an accessible style, the book offers students, business, government, and civil society players powerful insights on Asia.